PENGEMBANGAN FRAMEWORK MOBILE LEARNING PADA PERTANIAN SAYURAN - Erlangga Erlangga; Herbert Siregar; Yaya Wihardi (Jurnal Computech & Bisnis (e-Journal), 2020)
In vegetable production, farmers face many obstacles, such as the problems related to seeds, pest and disease control, commodity prices, and marketing of produces. There is almost no useful information and technology easily accessible to improve the situation. With the better penetration of the Internet to the villages and the wide availability of inexpensive mobile devices, mobile learning provides a good solution. This study is aimed to create a mobile learning framework that provides information and interactive communication about vegetable production needed by farmers. The method used was instructional design of ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Usability surveys of the proposed prototype to farmers, extension agents (field technical assistants), and researchers, result in 79.4%, 87.3%, and 87% satisfaction testing, respectively, in information needs fulfillment. Summative Testing in the aspect of User Acceptance Testing of validity and reliability indicated that the prototype could be used by farmers. Based on the assessment by experts, 87.3% of them agreed that the mobile learning framework for vegetable farming could provide learning information about vegetable production. Keywords: Mobile Learning, Mobile Learning Framework, Mobile Learning Agriculture, ADDIE (Analysis, Design, Development, Implementation, Evaluation)DOI: http://doi.org/10.5281/zenodo.3631040